2020
DOI: 10.5194/acp-20-15743-2020
|View full text |Cite
|
Sign up to set email alerts
|

UK surface NO2 levels dropped by 42 % during the COVID-19 lockdown: impact on surface O3

Abstract: Abstract. We report changes in surface nitrogen dioxide (NO2) across the UK during the COVID-19 pandemic when large and rapid emission reductions accompanied a nationwide lockdown (23 March–31 May 2020, inclusively), and compare them with values from an equivalent period over the previous 5 years. Data are from the Automatic Urban and Rural Network (AURN), which forms the basis of checking nationwide compliance with ambient air quality directives. We calculate that NO2 reduced by 42 %±9.8 % on average across a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 40 publications
9
34
0
Order By: Relevance
“…For metrics less influenced by nighttime concentrations (maximum 1 h, daily maximum 8 h, SOMO35, AOT40) the effect is smaller, leading to a more general reduction in the metric (the reduction in NOx emissions at higher radiation hours reduce O3 formation, leading to an improvement in air quality). These results are along the lines of the observed effect of COVID-19 lockdown emission reductions in the UK [20]. The authors found that a large reduction in NOx directly causes an increase in O3 due to a reduction in titration with NO (in addition to the fact that a warming climate may lead to increased emissions of biogenic VOCs).…”
Section: Discussionsupporting
confidence: 60%
“…For metrics less influenced by nighttime concentrations (maximum 1 h, daily maximum 8 h, SOMO35, AOT40) the effect is smaller, leading to a more general reduction in the metric (the reduction in NOx emissions at higher radiation hours reduce O3 formation, leading to an improvement in air quality). These results are along the lines of the observed effect of COVID-19 lockdown emission reductions in the UK [20]. The authors found that a large reduction in NOx directly causes an increase in O3 due to a reduction in titration with NO (in addition to the fact that a warming climate may lead to increased emissions of biogenic VOCs).…”
Section: Discussionsupporting
confidence: 60%
“…There are also short time period studies, which show even larger reduction of NO 2 [34]. In contrast, almost all studies also found increases of O 3 during the COVID-19 lockdown period, which was largely attributed to the reduction in NO emissions [27]. Note that these studies have taken use of different observations with various analysis methods over different locations.…”
Section: Introductionmentioning
confidence: 96%
“…Many studies have shown that the changes of air pollutants are different for periods before, during and after the outbreak [e.g., [23], [24], [25]], and the changes of pollutants are also diverse in different stages of lockdown periods [26]. Globally, as summarized by Lee et al [27], there are a consensus about the significant impacts of COVID-19 lockdown on air quality, while with different magnitudes of changes around the word. Particularly, almost all studies showed significant decrease in NO 2 during the lockdown time period, with decreasing amount of 42% in UK [27], 50% in Spain [28], 46% in Rome, 30% in Turin, 63% in Nice [29], 54% in New Delhi [30], 24-33% in Rio de Janeiro, Brazil, 54% in Sao Paulo [31], 21% in the whole of China [32], and 53% in Northern China [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid reduction in economic activity had many positive environmental impacts with the improvement of air quality being widely reported, especially via striking satellite observations of column NO 2 (Liu et al, 2020;Patel et al, 2020;Venter et al, 2020). Reductions in CO 2 emissions have also been reported globally due to heavily curtailed economic activities (Le Quéré et al, 2020;Forster et al, 2020). Many of the reports of improved air quality were preliminary, and further research was required to fully understand and quantify the improvements observed throughout Europe, particularly after accounting for meteorological factors (Grange et al, 2020;Carslaw, 2020;Lee et al, 2020;Wang et al, 2020;Shi et al, 2021;Fenech et al, 2021;Velders et al, 2021).…”
Section: Introductionmentioning
confidence: 99%